Do firms manage earnings during seasoned equity offerings - Xingzheng, Xiao (KDI School, 2011)
I examine earnings management around seasoned equity offerings in Australian Listed firms from 2002 to 2008. Seasoned equity issuers can raise reported earnings by altering discretionary accounting accruals. Consistent with prior studies (for example , Rangan, 1998 ; Lakshmanan, 2000; Yoon and Miller, 2002; Jo, Kim and Park, 2007; Guthrie and Sokolowsky, 2010; among many others ), I find that firms in Australia do manage their earnings in the year prior to seasoned equity offerings and the year of seasoned equity offerings, however, depending on different industries, some firms manage their earnings in the year prior to seasoned equity offering, for example, firms from industrials, consumer staples, health care and IT industry while other firms manage their earnings in the year of seasoned equity offering, for example, firms from the materials, industrials, consumer discretionary and consumer staples industry.
Thesis(Master) --KDI School:Master of Public Policy,2011
Keywords: Australia.